(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
On the Greek island of Chios, Lower Triassic sections bave delivered rich ammonoid faunas from red limestones of the Hallstatt facies. Here, we present a palaeontological description of Spathian ammonoids, which have been collected during two field campaigns by Italian-German teams (Assereto et al. 1980; Gaetani et al. 1992). The ammonoid associations are composed of Ceratitida and Phylloceratida, each order containing species of the Noritaceae, Hedenstroemiaceae, Xenodiscaceae, Dinaritaceae, Pinacocerataceae, Phyllocerataceae, Ptychitaceae, Ussuritaceae and Megaphyllitaceae. Long ranging genera, e.g. Procarnites and Leiophyllites, are present as well as endemic ones, e.g. Chiotites, which occurs exclusively in the Lower Triassic of Chios. The ammonoid association is indicative of the Prohungarites-Subcolumbites zone sensu Kummel (1973a). The haugi zone, installed as uppermost Olenekian in North America, is not represented by ammonoids on Chios.